The Use of Practicum-Based LKM Can Improve Concept Understanding in Science Subject Energy Materials - Ali Mustadi; Wahyu Kurniawati; Siti Munfaida (Jurnal Penelitian Pendidikan IPA, 2022)
This research is a research on the development of a practicum-based teaching material that aims to find out if the use of practicum-based student worksheets can increase conceptual understanding of energy material in natural science courses. Student worksheets are examples of learning media that are often used in teaching and learning activities. The method used in this research is a pre-experiment with a one-group pretest-posttest design. From the test results, the results are obtained if (1) Practicum-based Student Worksheet teaching materials have a good impact on increasing student understanding in science courses with energy material with an N-Gain score of 0.45. (2) The learning outcomes increased by 17.17 from the average pretest score of 62.7 to 80.47 at the end of the post-test results, which shows that student understanding has progressed after learning is carried out using practicum-based worksheets.